EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK DAN TALKING BREAD PADA POKOK BAHASAN GEOMETRI DAN PENGUKURAN DITINJAU DARI KECERDASAN MAJEMUK SISWA KELAS VIII SMP NEGERI SE-KABUPATEN KARANGANYAR - Sigit Pamungkas; Riyadi Riyadi; Budi Usodo (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objective of this research was to know the effect of the learning models on the learning achievement of quadrangle viewed from the multiple intellegences of the students. The learning models compared were the cooperative learning model type Talking Stick, the cooperative learning model type Talking Bread, and the direct learning models. The type of research was quasi-experimental research with factorial design 3×3. Population of this research was all students of State Junior High Schools in Karanganyar. The sampling was done by stratified cluster random sampling. The total samples in this research were 271 students (91 students for Talking Bread class, 90 students for talking stick class, and 90 students for direct learning class). The hypothesis test used two ways analysis of variance with unbalanced cells. Based on the hyotesis test, the research finding were : (1) learning activity using cooperative learning model type talking bread produced better echievement than using cooperative learning model type talking stick or direct learning. Learning activity using cooperative learning model type Talking Stick produced better than direct learning. (2) student with linguistic intelligence, space intelligence, and interpersonal intelligence produced the same achievement. (3) the usage of cooperative learning model type Talking Bread, cooperative learning model type Talking Stick, and direct learning produced the same achievement among the students with linguistic intelligence, space intelligence, and interpersonal intelligence. (4) toward students with linguistic intelligence, space intelligence, and interpersonal intelligence, cooperative learning model type Talking Bread produced better achievement than cooperative learning model type Talking Stick or direct learning, while cooperative learning model type Talking Stick produced the same achievement with direct learning model.Keywords: cooperative learning model, Talking Bread, Talking Stick, direct learning, student multiple intelligence, mathematic learning achievement.